2021
DOI: 10.1002/ajh.26286
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Life experience with hydroxyurea in patients with sickle cell disease: Results from the prospective ESCORT‐HU cohort study

Abstract: Several controlled studies have evidenced good efficacy and short-term and midterm safety profiles for hydroxyurea (HU), which has become the cornerstone for prevention of sickle-cell disease (SCD)-related vaso-occlusive crises. However, there are few large-scale reports on its long-term use and certain caregivers and patients have concerns about its safety. Following the licensing of HU in Europe for children and adults with severe forms of SCD, ESCORT-HU was designed as a Phase IV observational cohort study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 42 publications
(92 reference statements)
1
47
0
Order By: Relevance
“…and hydroxyurea have been considered as possible eventual causative factors, although there are no definitive findings so far. 30,31 Moreover, the largest lentiviral vector-mediated β-globin replacement gene therapy trial in SCD reported two cases of adult patients diagnosed with myeloid neoplasms, both considered unrelated to the gene therapy procedure, 32 as previously reported for patients with SCD undergoing BMT. 33,34 However, when we consider all hemoglobinopathies, BMT does not seem to be a major risk factor for cancer in our study, whereas the types of tumors detected in this group of patients indicate that the well-known risk of graft-vs-host disease-related cancers adds to that of a history of HCV and hepatic iron accumulation before BMT.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…and hydroxyurea have been considered as possible eventual causative factors, although there are no definitive findings so far. 30,31 Moreover, the largest lentiviral vector-mediated β-globin replacement gene therapy trial in SCD reported two cases of adult patients diagnosed with myeloid neoplasms, both considered unrelated to the gene therapy procedure, 32 as previously reported for patients with SCD undergoing BMT. 33,34 However, when we consider all hemoglobinopathies, BMT does not seem to be a major risk factor for cancer in our study, whereas the types of tumors detected in this group of patients indicate that the well-known risk of graft-vs-host disease-related cancers adds to that of a history of HCV and hepatic iron accumulation before BMT.…”
Section: Discussionmentioning
confidence: 77%
“…In this respect, a 72% increased risk of hematologic malignancies in patients with SCD in comparison with the general population was reported by Brunson et al 22 . Chronic inflammation and hydroxyurea have been considered as possible eventual causative factors, although there are no definitive findings so far 30,31 …”
Section: Discussionmentioning
confidence: 95%
“…This, however, has not definitively been ascertained. Experience suggests that HU is efficient and safe in young adults with ET [ 93 ] and that it does not induce adverse effects on growth and fertility when used in children with sickle-cell anemia [ 94 ]. However, HU might have different (and detrimental) effects in lifelong treatment for patients with a clonal diseases such as ET.…”
Section: Managing Thrombocythemia In Childrenmentioning
confidence: 99%
“…SCD affects approximately 100,000 people in the United States and millions globally, and every year an estimated 300,000 children are born with sickle cell anemia (SCA) across the globe [ 3 , 4 ]. Hydroxyurea (HU) is approved by the Food and Drug Administration for adults and children aged 2–18 years with SCD, but it is widely utilized in children beginning as early as 9 months of age [ 5 , 6 ]. Although HU has multiple therapeutic benefits in individuals with SCD, the primary benefits are through increasing fetal hemoglobin (HbF) and additionally increasing mean cell volume (MCV) and reducing absolute neutrophil count (ANC) and total white blood cell (WBC) counts.…”
Section: Introductionmentioning
confidence: 99%